Knowledge, attitudes, and practices on antimicrobial use and antimicrobial resistance among poultry practitioner veterinarians - Shahi, Manoj Kumar; Jeamsripong, Saharuetai (Frontiers in Veterinary Science, 2024)
Background: Antimicrobial resistance (AMR) poses a serious global threat to human and animal health. In the context of antimicrobial usage (AMU) in livestock production, veterinarians are key stakeholders. However, there is a lack of comprehensive situational analysis regarding the current Knowledge, Attitudes, and Practices (KAP) among veterinarians concerning AMU and AMR in poultry production in Nepal.The primary objective of this study was to evaluate the situation of AMU and KAP regarding AMU and AMR of among poultry practitioner veterinarians in Nepal. A total of 327 respondents from 56 districts across seven provinces participated. Demographic information and AMU situation were collected and analyzed using descriptive statistics, and factors affecting KAP on AMU and AMR were performed using logistic regression analysis.Results: Nearly half of veterinarians (49.2%) were from Bagmati, followed by Lumbini (16.5%) and Gandaki (8.9%) provinces. Most of the respondents (85.0%) identified themselves as male with a mean age of 31.9±7.8 years, with a range of 24 to 74 years. A large proportion of veterinarians held a master's degree (43.8%). Regarding reasons for AMR, 51.1% of them attributed it to the irrational use of antimicrobials. Other identified reasons for AMR, including over-the-counter sales (27.8%), low-dose administration (12.3%), and low-quality antimicrobials (6.7%). Based on antibiotic prescription rates, most veterinarians (50.8%) prescribed antimicrobials at a rate of 20-40%, while 25.9% prescribed at a rate of less than 20.0% and 18.9% at a rate of 40-60%. Approximately 89.0% of veterinarians agreed that vaccination could reduce the use of antimicrobials in poultry, and 75.6% preferred narrow-spectrum antimicrobials than broad-spectrum antimicrobials. A combination of broad-spectrum antimicrobials such as colistin with amoxicillin, gentamicin, tylosin, and tetracycline was commonly used in poultry production.In logistic regression analysis, it was observed that veterinarians aged 45-60 years demonstrated significantly higher levels of knowledge concerning AMU and AMR (p = 0.02) compared to those in the 24-30 age group. This study indicates that the need for robust regulatory mechanisms in veterinary drug administration and increased awareness among veterinarians to address the AMR issue livestock production.